Home Industrial Return Analysis Shrimp Cap Obor Tegal City: Analisis Keuntungan Home Industri Terasi Udang rebon Cap Obor Kota Tegal - Natasya Natasya Febrian Camila; Suci Nur Utami; Muhammad Dini Adita (Journal of Agribusiness and Community Development (AGRIVASI) UMUS, 2021)
The shrimp paste business is a potential business in Tegal City, it is supported by abundant marine products and a large number of businesses engaged in processing fishery products. However, to find out whether the business has the potential to continue to grow or not, an R/C Ratio analysis is needed. The research location is in the Home Industry of Terasi dan kerupuk Obor Tegal City, from the results of the analysis, the R/C Ratio value is 3.885 with a profit value of Rp. 21,834,129.12 in the production period in May 2022. From the value of the R/C ratio above, it can be concluded that the business is very profitable and feasible to continue to be developed.